2009
DOI: 10.1038/pcan.2009.19
|View full text |Cite
|
Sign up to set email alerts
|

Impact of capsular incision on biochemical recurrence after radical perineal prostatectomy

Abstract: The prognostic implications of capsular incision (CI) remain to be defined. We evaluated the impact of CI on biochemical recurrence (BCR) and the potential risk factors of CI. Between June 1995 and July 2007, 266 patients with follow-up for at least 6 months, who had neither the seminal vesicle nor lymph node involvement on prostatectomy specimen, were included. Patients with insufficient biopsy data and those with neoadjuvant and/or adjuvant therapy were excluded. CI was defined as tumor extending into the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 32 publications
(34 reference statements)
0
21
1
Order By: Relevance
“…In our previous reports, isolated IPI rates in OC disease ranged from 1.8% to 2.3% [8,16]. However, others reported the IPI rates in OC disease as high as 20% [9,15]. This variation in IPI rate can be partly attributed to pathologic interpretation.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In our previous reports, isolated IPI rates in OC disease ranged from 1.8% to 2.3% [8,16]. However, others reported the IPI rates in OC disease as high as 20% [9,15]. This variation in IPI rate can be partly attributed to pathologic interpretation.…”
Section: Discussionmentioning
confidence: 89%
“…IPI in the RP specimen is associated with an increased risk of progression following surgery [57,9]. Most studies that evaluated the prognostic significance of IPI reported the IPI rate in men with organ-confined (OC) disease only [69,15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results compare favourably with rates obtained by Kwak and colleagues. 23 In their cohort, they reported 15.6% of PSM for organ-confined disease. Although contralateral disease was common, it was associated with a low risk of extension beyond the contralateral capsule.…”
Section: Discussionmentioning
confidence: 95%